The Role of Perceived Ease of Use, Trust and Perceived Usefulness on Intention to Use Customer of Tix Id - Kartika Sari; Sherry Adelia; Ni Made Yusmini; Hasmidar; Agus Nurofik (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The objectives of this study is to examine the influence of perceived ease of use, trust and perceived usefulness toward intention to use of customer of Tix Id. This study is using a quantitative approach because the data used is in the form of numbers and was calculated using statistical methods. This study aims to analyze the causal relationship between perceived usefulness, perceived ease of use, and trust and the dependent variable, namely, the intention to use Dana in Tix Id. In order to focus more on the research being conducted, the scope of the research is focused only on users who are in South Jakarta and South Tangerang from March to August 2022. Result of this study is perceived usefulness in terms of saving time and money when purchasing a product or service has no effect on intention to use. Perceived ease of use, related to the ease of learning, understanding, and clarity in using a technology and making it easier for technology to do what users want it to do, has a significant positive influence on intention to use.